Study on the influence of scaffold morphology and structure on osteogenic performance - Zhou, Jingyu; Xiong, Shilang; Liu, Min; Yang, Hao; Wei, Peng; Yi, Feng; Ouyang, Min; Xi, Hanrui; Long, Zhisheng; Liu, Yayun; Li, Jingtang; Ding, Linghua; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
The number of patients with bone defects caused by various bone diseases is increasing yearly in the aging population, and people are paying increasing attention to bone tissue engineering research. Currently, the application of bone tissue engineering mainly focuses on promoting fracture healing by carrying cytokines. However, cytokines implanted into the body easily cause an immune response, and the cost is high; therefore, the clinical treatment effect is not outstanding. In recent years, some scholars have proposed the concept of tissue-induced biomaterials that can induce bone regeneration through a scaffold structure without adding cytokines. By optimizing the scaffold structure, the performance of tissue-engineered bone scaffolds is improved and the osteogenesis effect is promoted, which provides ideas for the design and improvement of tissue-engineered bones in the future. In this study, the current understanding of the bone tissue structure is summarized through the discussion of current bone tissue engineering, and the current research on micro-nano bionic structure scaffolds and their osteogenesis mechanism is analyzed and discussed.